2013
DOI: 10.1097/mib.0b013e3182802a0a
|View full text |Cite
|
Sign up to set email alerts
|

The Overlap of Functional Abdominal Pain in Pediatric Crohn’s Disease

Abstract: Background Children with Crohn’s disease (CD) may report abdominal pain despite clinical remission, suggesting that functional abdominal pain (FAP) may be playing a role. Aim This study aims to explore the presence and impact of FAP in children with CD in remission. Methods Children, aged 9–17, with CD were enrolled. Demographic information, the Pediatric Crohn’s Disease Activity Index (PCDAI), and the Children’s Depression Inventory (CDI) were obtained. Disease remission was defined by physician global as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 30 publications
0
62
1
1
Order By: Relevance
“…However, disabling chronic abdominal pain is present in a subset of patients with inactive or mildly active IBD [4, 5]. Although there is adult data citing abdominal pain rates of 20%–50% during remission (presumed functional abdominal pain) [6], there is a paucity of pediatric data on rates of abdominal pain and functional abdominal pain (visceral hypersensitivity) in IBD [7, 8]. The largest of existing studies conducted by Zimmerman et al [7] revealed rates of 45% in their 307 patients; with 13% meeting their criteria for functional abdominal pain (as defined by abdominal pain during disease remission).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, disabling chronic abdominal pain is present in a subset of patients with inactive or mildly active IBD [4, 5]. Although there is adult data citing abdominal pain rates of 20%–50% during remission (presumed functional abdominal pain) [6], there is a paucity of pediatric data on rates of abdominal pain and functional abdominal pain (visceral hypersensitivity) in IBD [7, 8]. The largest of existing studies conducted by Zimmerman et al [7] revealed rates of 45% in their 307 patients; with 13% meeting their criteria for functional abdominal pain (as defined by abdominal pain during disease remission).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is adult data citing abdominal pain rates of 20%–50% during remission (presumed functional abdominal pain) [6], there is a paucity of pediatric data on rates of abdominal pain and functional abdominal pain (visceral hypersensitivity) in IBD [7, 8]. The largest of existing studies conducted by Zimmerman et al [7] revealed rates of 45% in their 307 patients; with 13% meeting their criteria for functional abdominal pain (as defined by abdominal pain during disease remission). Furthermore, though adult studies have shown patients with Crohn’s disease (CD) (compared to those with ulcerative colitis (UC)) have a higher degree of abdominal pain [911] and are more likely to be on narcotics [12], and a recent meta-analysis did note higher rates of Irritable Bowel Syndrome (IBS; which includes abdominal pain as a symptom) in CD compared to UC [13], there are no pediatric studies comparing rates of abdominal pain (or functional abdominal pain) between CD and UC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2023)It is often unrelated to the degree of IBD inflammation and termed “functional” abdominal pain. From a clinical perspective, depressive coping style is more predictive than medical variables for disease-related concerns (including reports of abdominal pain) providing insight into mechanisms of depression leading to abdominal pain.…”
Section: Introductionmentioning
confidence: 99%
“…These findings highlight the importance of measuring pain in addition to understanding patients' disease state, as it appears that the presence of pain with active disease, rather than active disease alone, may place these patients at higher risk for emotional distress or that increased emotional distress may in turn color patients' report of pain. In fact, Zimmerman et al, (17) recently found that the experience of abdominal pain, rather than disease activity, was associated with higher levels of depression for pediatric patients with CD. Similarly, Srinath and colleagues (35) found that depression, rather than biological disease markers, was associated with reports of abdominal pain for pediatric patients with CD.…”
Section: Discussionmentioning
confidence: 99%